(untitled) (Journal on studies and research of academic knowledge, 2022)
The pandemic caused by the SARS-CoV-2 virus, the triggering factor for the Covid-19 disease, starts in Wuhan, China. In Paraguay, the first case of Covid-19 infection was detected on March 7th, 2020. Since then, the number of cases raised month by month until the virus was spread around the entire country. The objective of this study was to evaluate the epidemiological characteristics of patients with SARS-CoV-2 virus in samples from the Molecular Biology Laboratory of the Regional Hospital of Encarnación, Itapúa-Paraguay from August 2020 until January 2021, using epidemiological data from the General Directorate of Health Surveillance. A descriptive, prospective, cross-sectional study was carried out, 11,400 samples identified by the qRT-PCR technique were processed, of which 2,193 were positive, with a higher incidence in the months of October 2020 and January 2021 in Itapúa. Most of the cases corresponded to the female sex (54.17%). The 85,13% of the patients exhibited symptoms. The months that registered peak cases were October and January. The age range with the highest percentage of infections was from 21 to 30 years old. The identified most frequent symptoms were headaches, nasal congestion, cough, and sore throat. The median of Ct values decreased in January, and the average values for E and RdRp 2 genes were lower than ORF1ab and N genes. On the whole, epidemiology characteristics of Covid-19 positive patients were described in the analyzed period